1983
DOI: 10.1530/acta.0.1040287
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hypothalamic extracts and TRH on the growth and hormone production of GH3 cells in culture

Abstract: Hypothalamic factors were tested for their effects on the production of hormones and the growth of GH3 cells, cloned rat pituitary cells producing prolactin (Prl) and growth hormone (GH). Hypothalamic extracts (HE) (0.05 mg/ml) and TRH (0.3 \g=m\m)stimulated the synthesis of Prl to levels of 306% and 360%, respectively, of the control culture in a medium containing 0.5% foetal bovine serum (FBS) during a 24 h incubation. They did not affect the rate of GH production. The thymidine uptake was suppressed to 57% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It has been shown that GH3 cells retain their ability to respond to TRH (14), epidermal growth factor (EGF) (15,16) and nerve growth factor (NGF) (17). Recent studies have demonstrated that activin receptors (typeIA, typeII and typeIIB) are present on GH3 cells (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that GH3 cells retain their ability to respond to TRH (14), epidermal growth factor (EGF) (15,16) and nerve growth factor (NGF) (17). Recent studies have demonstrated that activin receptors (typeIA, typeII and typeIIB) are present on GH3 cells (18,19).…”
Section: Introductionmentioning
confidence: 99%